Differential Item Functioning at the scal of mental health (Journal Of Educational and Psychological Researches, 2011)
At the last years, the interesting of measurement spicilists was increased to study differential item functioning (DIF) wich is reflect the difference of propability true response for test item from subgroups which have equal level of ability . The aims of this research are, inform the DIFat Namers’scale(2009) for mental health to prepare students and detect items that have DIF. Sample research contants (540) students, we use Mantel- Haenzel chi-square to detect DIF. The results are point to there are (26) items have DIF according to gender which are delated form the scale after that.